2018
DOI: 10.20448/2001.41.42.46
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Human Nature and Implications for Research in the Behavioural Sciences

Abstract: This paper examined the perspectives of human behaviour as a precursor to determine the methodological preference for inquiry into the knowledge of its complex and intricate nature. The paper identified some fundamental taxonomies of action, expressed in human action, social action, purposive action, environmentally constrained action, and emergent process action. These constitute perspectives on action that are broadly categorized into prospective and retrospective perspectives on action. The prospective view… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…Finally, the imitative characteristics of institutional theory could be helpful in visualizing the present constraints of risk reporting. In fact, application of these designated complementary and interconnecting theories ensures greater insight than using just one economic theory (Cormier et al, 2005;Eketu, 2018).…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…Finally, the imitative characteristics of institutional theory could be helpful in visualizing the present constraints of risk reporting. In fact, application of these designated complementary and interconnecting theories ensures greater insight than using just one economic theory (Cormier et al, 2005;Eketu, 2018).…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…Similarly, the results also found the significant positive contribution of intellectual capital on the financial performance of Chinese technology firms. Using the measure of green customer capital, also examined the impact of relationship learning on firm's ecologically driven intellectual capital and innovation performance (Eketu, 2018;Dawabsheh et al, 2019). In doing so, the authors used the data of manufacturing companies in Spain.…”
Section: Gicmentioning
confidence: 99%
“…Previous studies have provided different views in relation to the impact of board size. A group of studies have found larger board size is more effective in managing a company (Pearce & Zahra, 1992;Goodstein, Gautam & Boeker, 1994;Abdul Rahman & Mohamed Ali, 2006;Eketu, 2018). They suggested that more human capitals and brains might contribute to more physical attribution and ideas into the companies.…”
Section: Board Sizementioning
confidence: 99%